2014
DOI: 10.1103/physreve.90.052119
|View full text |Cite
|
Sign up to set email alerts
|

From explosive to infinite-order transitions on a hyperbolic network

Abstract: We analyze the phase transitions that emerge from the recursive design of certain hyperbolic networks that includes, for instance, a discontinuous ("explosive") transition in ordinary percolation. To this end, we solve the q-state Potts model in the analytic continuation for non-integer q with the real-space renormalization group. We find exact expressions for this one-parameter family of models that describe the dramatic transformation of the transition. In particular, this variation in q shows that the disco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[4], or in field theory, where it signals the loss of conformality [39]. However, it is most closely related to the recent observation of discontinuous ("explosive") transitions in ordinary percolation on hierarchical networks [18,20,28,40]. Our study shows that criticality in these models is generally non-universal but falls into three generic regimes.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…[4], or in field theory, where it signals the loss of conformality [39]. However, it is most closely related to the recent observation of discontinuous ("explosive") transitions in ordinary percolation on hierarchical networks [18,20,28,40]. Our study shows that criticality in these models is generally non-universal but falls into three generic regimes.…”
mentioning
confidence: 54%
“…In particular, the iterative structure of hierarchical networks may facilitate their realization in engineered devices to unlock and control their unconven-tional behaviors. Work on percolation [15][16][17][18][19][20], the Ising model [21][22][23][24][25], and the q-state Potts model [26][27][28] have shown that critical behavior, once thought to be exotic and model-specific [4], can be categorized with the renormalization group [26] for a large class of hierarchical networks with a hyperbolic structure.…”
mentioning
confidence: 99%
“…Certain hierarchical networks, with a self-similar structure and small-world connections, have shown to exhibit novel dynamics [16][17][18][19][20][21]. Here, we design hierarchical models based on one such example, the Hanoi networks [16,18,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These networks are well suited to perform exact real-space renormalization group (RG) calculations. Using RG theory there has been very important progress in characterizing the critical properties of percolation [14][15][16][31][32][33][34][35][36], spin (Ising and Potts) models [37][38][39][40], and Gaussian models [25,26] in these structures. In particular in Refs.…”
Section: Introductionmentioning
confidence: 99%